Redevelopment of Pinaglabanan Memorial Shrine an urban recreational community centre - Ngo, Francis Matthew O.
This project aims to study how visual connection and views would be a tool to bridge and enrich a place's historical and cultural significance to its everyday users. In addition to responsive design and a design that answers to a user's needs, the project aims to study and investigate how views are essential and enriching to a user's experience through space -- while also aiming that this experience deepens and furthers their understanding and appreciation to a historical structure or place of history and culture. the Pinaglabanan Memorial Shrine is a place of history and culture, yet most of the users do not essentially know about this. This shrine's identity is seen more as a public park, and it is understandable since it is San Juan City's only large public space. The project then investigates how architecture can address the needs of the users and at the same time bridge and enrich the space as a historical and cultural site. The projects explore that, yes, the place is now seen as a place of recreation yet how can architecture link the users and the place's culture and history.